Flowering fires = Fuegos florales - Partnoy, Alicia. (Midnight Editions, 2015)
Recipient of the first annual Settlement House American Poetry Prize, Alicia Partnoy's "Flowering Fires / Fuegos Florales" is a work of wisdom born of witness and tempered by a lifetime of commitment to her craft. Gail Wronsky's translations render this poems as vital in English as they are in Spanish. This is a book to be cherished, read and reread.